Mechanisms and feasibility of prey capture in ambush-feeding zooplankton - Kiørboe, Thomas (National Academy of Sciences, 2009)
Many marine zooplankters, particularly among copepods, are “ambush feeders” that passively wait for their prey and capture them by fast surprise attacks. This strategy must be very demanding in terms of muscle power and sensing capabilities, but the detailed mechanisms of the attacks are unknown. Using high-speed video we describe how copepods perform spectacular attacks by precision maneuvering during a rapid jump. We show that the flow created by the attacking copepod is so small that the prey is not pushed away, and that the attacks are feasible because of their high velocity (≈100 mm·s(−1)) and short duration (few ms), which leaves the prey no time for escape. Simulations and analytical estimates show that the viscous boundary layer that develops around the attacking copepod is thin at the time of prey capture and that the flow around the prey is small and remains potential flow. Although ambush feeding is highly successful as a feeding strategy in the plankton, we argue that power requirements for acceleration and the hydrodynamic constraints restrict the strategy to larger (> 0.25 mm), muscular forms with well-developed prey perception capabilities. The smallest of the examined species is close to this size limit and, in contrast to the larger species, uses its largest possible jump velocity for such attacks. The special requirements to ambush feeders with such attacks may explain why this strategy has evolved to perfection only a few times among planktonic suspension feeders (few copepod families and chaetognaths).